DUOX1 Silencing in Mammary Cell Alters the Response to Genotoxic Stress. (19th April 2018) - Fortunato, Rodrigo S.; Gomes, Luciana R.; Munford, Veridiana; Pessoa, Carolina Fittipaldi; Quinet, Annabel; Hecht, Fabio; Kajitani, Gustavo S.; Milito, Cristiane Bedran; Carvalho, Denise P.; Menck, Carlos Frederico Martins
Abstract : DUOX1 is an H2 O2 -generating enzyme related to a wide range of biological features, such as hormone synthesis, host defense, cellular proliferation, and fertilization. DUOX1 is frequently downregulated in lung and liver cancers, suggesting a tumor suppressor role for this enzyme. Here, we show that DUOX1 expression is decreased in breast cancer cell lines and also in breast cancers when compared to the nontumor counterpart. In order to address the role of DUOX1 in breast cells, we stably knocked down the expression of DUOX1 in nontumor mammary cells (MCF12A) with shRNA. This led to higher cell proliferation rates and decreased migration and adhesion properties, which are typical features for transformed cells. After genotoxic stress induced by doxorubicin, DUOX1-silenced cells showed reduced IL-6 and IL-8 secretion and increased apoptosis levels. Furthermore, the cell proliferation rate was higher in DUOX1-silenced cells after doxorubicin medication in comparison to control cells. In conclusion, we demonstrate here that DUOX1 is silenced in breast cancer, which seems to be involved in breast carcinogenesis.